The Implementation of Project-Based Learning to Improve Students’ Participation and Interaction in Learning Arabic Language: A Focus on Writing Skills - Fitria Fitria; Munirul Abidin (P3M IAI Nusantara Batang Hari, 2023)
One of learning models that has recently been widely applied is Project-based Learning (PJBL). PJBL is a learning model that provides space for educational actors who are directly involved in the classroom, namely teachers and students, to be jointly involved in a project to solve a problem. PJBL is widely applied to learning hard sciences such as Physics. So far, discussion of learning models that use PJBL in Arabic subjects is still relatively limited. This research aims to fill in the gaps in research and knowledge related to how to apply PJBL in learning Arabic in secondary education, especially in writing skills with the topics